Combined Application of Phosphorus Fertilizer with Tithonia Biomass Improves Grain Yield and Agronomic Phosphorus Use Efficiency of Hybrid Maize. (1st July 2019) - Endris, Solomon
Abstract : Low soil phosphorous level is among several constraints limiting crop productivity in southwestern Ethiopia. The dominant soil types in the region are acidic nitosols that are low in plant-available phosphorus. Most farmers cultivate maize with minimal external inputs and hence result in suboptimal yield levels. The effect of applying Tithonia biomass and phosphorus fertilizer on the agronomic efficiency of phosphorus and yield of maize was therefore investigated in a randomized complete block design with three replications. Tithonia ( Tithonia diversifolia ) biomass and Triple Superphosphate (TSP) were used as organic and inorganic sources of phosphorus, respectively. Significant treatment differences (P < 0.01 ) were observed for most of the parameters studied including agronomic efficiency, partial factor productivity (PFP), and grain yield. Agronomic phosphorus use efficiency increased from 26.3 at the sole TSP to 163 at treatment 7, a staggering 520% increment when combined with Tithonia biomass. Similarly, PFP of phosphorus increased from 169.1 to 324.8. At the same time, 53% increment of the grain yield was recorded over the control. Although applying the highest Tithonia biomass alone gave the highest grain yield, application of just 50% of the highest rate of Tithonia biomass and TSP looks more appealing to smallholder maize producers in the region. The result therefore indicated that Tithonia biomass could be utilized in smallholder maize production system as a source of plant nutrients such as phosphorus; it also emphasized the need to allot more resources and attention in exploring locally available and cheap sources of plant nutrients which could augment crop productivity amid the mounting financial challenges faced by farmers in the region.